2005
DOI: 10.1111/j.0965-075x.2005.00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Self-Other Agreement: Comparing its Relationship with Performance in the U.S. and Europe

Abstract: The use of multi‐source feedback has proliferated in the United States in recent years; however, its usefulness in other countries is unknown. Using a large sample of American managers (n=3793), this study first replicated earlier studies demonstrating that simultaneous consideration of self and other ratings of leadership skills is important for managerial performance ratings. In addition, the impact of self–other agreement on performance was investigated among 2732 managers in five European countries (U.K., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
95
3
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 35 publications
8
95
3
2
Order By: Relevance
“…Although previous studies have concluded that over-estimators are generally poor performers and less effective (e.g., Atwater et al, 2005;Ostroff et al, 2004;Tekleab et al, 2008;, there are nevertheless some indications that this picture is more nuanced. For example, Atwater et al (1998) found that leaders who received high ratings from others (i.e., peers and subordinates) but provided still higher self-ratings were rated as more effective by their direct supervisor.…”
Section: Self-other Agreement and Leader Effectivenessmentioning
confidence: 95%
See 4 more Smart Citations
“…Although previous studies have concluded that over-estimators are generally poor performers and less effective (e.g., Atwater et al, 2005;Ostroff et al, 2004;Tekleab et al, 2008;, there are nevertheless some indications that this picture is more nuanced. For example, Atwater et al (1998) found that leaders who received high ratings from others (i.e., peers and subordinates) but provided still higher self-ratings were rated as more effective by their direct supervisor.…”
Section: Self-other Agreement and Leader Effectivenessmentioning
confidence: 95%
“…However, our hypothesis regarding turnover intention appears to have indirect support in that turnover intention has been shown to have significant association with job satisfaction in a number of studies. For example, Tett and Meyer (1993) Atwater et al (2005) found that only others' ratings were significant in the prediction of leader performance in five European countries; that is, self-rating and the interaction between self and others' ratings played an insignificant role. In contrast, they found both self and others' ratings to be significant predictors in the United States.…”
Section: Self-other Agreement and Subordinates' Job Satisfaction And mentioning
confidence: 99%
See 3 more Smart Citations